Advances and applications in computer science, electronics and industrial engineering : proceedings of the Conference on Computer Science, Electronics and Industrial Engineering (CSEI 2019) /: proceedings of the Conference on Computer Science, Electronics and Industrial Engineering (CSEI 2019). ([2020]) - Unknown
No abstract available